Solar-Powered Smart Bus Shelter in UTHM Campus - Chong, Xian Ming; Othman, Nurmiza (Journal of Electronic Voltage and Application, 2025)
This project involves the designing and implementation of solar-powered smart bus shelters within the UTHM campus. The current UTHM bus shelter faces challenges such as lacking real-time information, safety issues due to a lack of lighting support, and bad student experiences while waiting for a bus due to hot or bad weather. Therefore, this project seeks to enhance the students or passengers experience when they want to board on the bus and the bus shelter could provide real-time bus location display, LED lighting, and fans powered by clean solar energy. Incorporating the Internet of Things, the smart bus shelter provides the students with precise real time bus location information that enhances their safety and convenience. Besides that, the smart bus shelter also provides a messenger to notify students which bus approaches which bus shelter in order to reduce the possibility of students missing chances of boarding on the correct bus. The project helps in sustainable development by reducing energy consumption and supporting environmentally friendly public transport solutions. By extensive testing and evaluation, the performance and reliability of the prototype are validated, proving its potential in transforming the conventional bus shelter into the intelligent energy-saving system.